Pengembangan Sistem Employee Self Service (ESS) Berbasis Web Terintegrasi Dengan Kinerja Karyawan (Studi Kasus: Astrido Group) - Wibowo, Satria Ardi; Susanto, Agung Budi; Anggai, Sajarwo (Universitas Pamulang, 2024)
Technological developments in the 4.0 era require humans to act effectively and efficiently. Astrido Group is a company operating in the automotive sector, especially car sales and services. The expected goal of this research is to build an information sistem that makes it easier for employees to update personal data, download attendance reports, process leave applications and approvals and obtain employee performance information. The sistem development method is Rapid Application Development (RAD) and modeled using the Unified Modeling Language (UML). Focus Group Discussion (FGD) Used as validation testing. The resulting software quality test is based on the four software quality characteristics of the ISO 9126 model, namely: functionality, reliability, usability and efficiency which are combined using the questionnaire method. The Black Box test results were 100%, which indicates the system was well received by users, while testing with Acunetix WVS was at Threat Level 2, which indicates the application being built is quite safe.